Uncovering undetected hypoglycemic events - Unger J (Dove Medical Press, 2012)
Jeff UngerCatalina Research Institute, Chino, CA, USAAbstract: Hypoglycemia is the rate-limiting factor that often prevents patients with diabetes from safely and effectively achieving their glycemic goals. Recent studies have reported that severe hypoglycemia is associated with a significant increase in the adjusted risks of major macrovascular events, major microvascular events, and mortality. Minor hypoglycemic episodes can also have serious implications for patient health, psychological well being, and adherence to treatment regimens. Hypoglycemic events can impact the health economics of the patient, their employer, and third-party payers. Insulin treatment is a key predictor of hypoglycemia, with one large population-based study reporting an overall prevalence of 7.1% (type 1 diabetes mellitus) and 7.3% (type 2 diabetes mellitus) in insulin-treated patients, compared with 0.8% in patients with type 2 diabetes treated with an oral sulfonylurea. Patients with type 1 diabetes typically experience symptomatic hypoglycemia on average twice weekly and severe hypoglycemia once annually. The progressive loss of islet cell function in patients with type 2 diabetes results in a higher risk of both symptomatic and unrecognized hypoglycemia over time. Patients with diabetes who become hypoglycemic are also more susceptible to developing defective counter-regulation, also known as hypoglycemia awareness autonomic failure, which is life-threatening and must be aggressively addressed. In patients unable to recognize hypoglycemia symptoms, frequent home monitoring or use of continuous glucose sensors are critical. Primary care physicians play a key role in the prevention and management of hypoglycemia in patients with diabetes, particularly in those requiring intensive insulin therapy, yet physicians are often unaware of the multitude of consequences of hypoglycemia or how to deal with them. Careful monitoring, adherence to guidelines, and use of optimal treatment combinations are all important steps toward improving care in patients with diabetes. The most important goals are for primary care physicians to recognize that every patient treated with antihyperglycemic medications is at risk of iatrogenic hypoglycemia and to ask patients about hypoglycemia at every visit.Keywords: hypoglycemia, insulin analogs, type 1 diabetes mellitus, type 2 diabetes mellitus